The effect of canopy architecture on the patterning of “windflecks” within a wheat canopy - Burgess, Alexandra J.; Durand, Maxime; Gibbs, Jonathon A.; Retkute, Renata; Robson, T. Matthew; Murchie, Erik H. (Plant, cell and environment, 2021)
Under field conditions, plants are subject to wind‐induced movement which creates fluctuations of light intensity and spectral quality reaching the leaves, defined here as windflecks. Within this study, irradiance within two contrasting wheat (Triticum aestivum) canopies during full sun conditions was measured using a spectroradiometer to determine the frequency, duration and magnitude of low‐ to high‐light events plus the spectral composition during wind‐induced movement. Similarly, a static canopy was modelled using three‐dimensional reconstruction and ray tracing to determine fleck characteristics without the presence of wind. Corresponding architectural traits were measured manually and in silico including plant height, leaf area and angle plus biomechanical properties. Light intensity can differ up to 40% during a windfleck, with changes occurring on a sub‐second scale compared to ~5 min in canopies not subject to wind. Features such as a shorter height, more erect leaf stature and having an open structure led to an increased frequency and reduced time interval of light flecks in the CMH79A canopy compared to Paragon. This finding illustrates the potential for architectural traits to be selected to improve the canopy light environment and provides the foundation to further explore the links between plant form and function in crop canopies. High‐resolution analysis indicates sub‐second changes in solar spectral irradiance in wheat (Triticum aestivum) canopies subject to wind‐induced movement. Such changes can be linked to architectural traits with potential consequences for photosynthetic productivity.